Gambaran Persepsi Risiko terhadap bencana pada Remaja di Wilayah DKI Jakarta - Christiany Suwartono; Eko Aditya Meinarno (Jurnal Ilmiah Psikologi MIND SET, 2009)
The purpose of this research was to gain understanding and experience of individual's risk perception. The research method was quantitative, using risk perception questionnaire (159 questions), adapted from Kpanake, Chauvin and Mullet (2008). The participants of this research were 123 Jakarta residents consisting of 98 females and 125 males. The results were put in five broad categories of risks: (1) natural disasters, (2) wars, (3) chemicals, (4) human relationships and (5) health. Natural disasters include tsunami and earthquake. Wars consist of battles, nuclear weapons, chemical weapons and dynamites. Chemical contain of ecstasy, heroin, and hospital wastes. Human relationships include sexual intercourse, crimes, and violence. One risk perception in health is heart surgery. The results of the research are somewhat different from Slovic, Fischhoff and Lichenstein's findings (1979) revealing that nuclear usage is the number one issue. This is due to the difference in research's conditions. Their research was conducted in US which have nuclear weapons and suffered several nuclear reactor accidents. On the other hand, Indonesia is not only an archipelago on actively moving earth crusts resulting on earthquakes and volcano eruptions but also undergoes destructive natural resource exploitation leading to floods and landslides.